Biopolitics and Democracy as a Lifestyle: A View from Social Psychology - Díaz Gómez, Álvaro; Carmona, Olga Lucía; Salamanca, Liliana Andrea (Pensando Psicología, 2018)
Purpose: To reflect on two ways of adopting democracy, as a form of government and as a way of life, in order to establish its relationship with biopolitics from social psychology—as a psychology that is political—based on a particular case that occurred in Colombia known as “false positives.”Theme: The possibility of thinking about a life that is politically controlled from the perspective of social psychology, for which it is assumed from the discourse of biopolitics.Elaboration: A contextualization is provided for recognizing that social psychology is political given the use of the knowledge it produces, so that problems that emerge in the construction of democracy cannot be alien to it and, thus, it is plausible to approach its expression as a lifestyle in relation to what it is as a form of government. From this, biopolitical devices for life control are established, and the extrajudicial executions implemented in Colombia, known as “false positives,” are an example of this.Conclusions: It is still visible how psychology, particularly social psychology, is political because of the way knowledge is used. Therefore, if thought in terms of popular majorities, knowledge may contribute to the construction of a democratic society, in which it is not only a structural governmental process but also deployed as a cultural ethos in daily life. Perhaps this is how processes of resistance to biopolitics are generated and a psychopolitics emerges.
Keywords: biopolitics; democracy as a way of life; democracy as a form of government; false positives; social psychology; politics